Ablation index value for transmural lesions based on unipolar electrograms in patients with paroxysmal atrial fibrillation undergoing pulmonary vein isolation - Yijun Sun; Yijun Sun; Binhao Wang; Binhao Wang; Mingjun Feng; Mingjun Feng; Yibo Yu; Yibo Yu; Fang Gao; Fang Gao; Weidong Zhuo; Weidong Zhuo; et al. (Frontiers in Cardiovascular Medicine, 2024)
BackgroundIt remains unclear whether the current recommended ablation index (AI) value is suitable for individualized catheter ablation. Prior research has established that the elimination of the negative component of the unipolar electrogram (UP-EGM) applications reflects the formation of transmural lesion during radiofrequency ablation. The aim of this study was to explore the relationship between AI values when UP-EGM turns positive during pulmonary vein isolation and recommended AI values.MethodsA total of 50 patients with drug-refractory PAF who underwent index RFCA were consecutively included from September 2022 to January 2023. All the patients underwent AI-guided ablation. UP-EGM was also recorded during the procedure. The difference in the AI between the value when the UP-EGM turned completely positive [AIUP-EGM(+)] and the recommended value at the end of ablation (AIEND) was compared.ResultsA total of 2 954 lesion points were detected in 50 patients. The average values of AIUP-EGM(+) at the anterior wall and the posterior wall were 420.9 and 267.4, respectively. The average AIEND values were 524.3 and 393.9 at the anterior wall and the posterior wall, respectively. The percentage of increase in the AI between the AIUP-EGM(+) and AIEND groups was 22%, 28% at the anterior wall and 47%, 49% at the posterior wall (P < 0.001). After a mean follow-up duration of 11.30 ± 2.10 months, 44 patients (88%) remained in sinus rhythm without antiarrhythmic drugs.ConclusionThe AIUP-EGM(+) was lower than the recommended value for all the pulmonary vein regions. The recommended AI value seems to be too high for the posterior and inferior walls, but this remains to be proven in future research.